Race, gender and stroke subtypes mortality in São Paulo, Brazil Raça, gênero e mortalidade por subtipos da doença cerebrovascular em São Paulo, Brasil - Paulo A. Lotufo; Alessandra C. Goulart; Isabela M. Bensenor (Arquivos de Neuro-Psiquiatria, 2007)
Stroke mortality rates have a discrepant distribution according to socioeconomic variables as social exclusion in Brazil. Recently, data from race has been available from the official health statistics considering five categories: White, Mixed, Black, Asian and Native. We addressed in the city of São Paulo, Brazil, an analysis of cerebrovascular mortality according to race (excluding Asian and Native due to small number of events) and gender during 1999-2001 for people aged 30 to 79 years-old. For all cerebrovascular diseases, age-adjusted mortality rates (x 100,000) for men were higher for Black (150.2), intermediate for Mixed (124.2) and lower for White (104.5) people. These gradient patterns were similar for all stroke subtypes, except for subarachnoideal hemorrhage in which no differences were detected. For women, the rates were lower compared to men and the same pattern was observed among Black (125.4), Mixed (88.5) and White (64.1) women. Compared to White men, the risk ratio of Black men was 1.4. However, compared to White women, the risk ratio for Black women was 2.0. Concluding, there is a significant gradient of stroke mortality according to race, mainly among women. As taxas de mortalidade pela doença cerebrovascular apresentam distribuição diferenciada de acordo com variáveis socioeconômicas. Informação sobre raça é nova no sistema de informação de mortalidade do Ministério da Saúde. Na cidade de São Paulo foi verificada entre três categoria de raça - branca, parda e negra - a taxa específica de mortalidade nos anos de 1999-2001 para pessoas entre 30 e 79 anos. Para o conjunto das doenças cerebrovasculares as taxas de mortalidade ajustadas para idade (x 100.000) para homens foram maiores entre os negros (150,2), intermediária para os pardos (124,2) e menor para brancos (104,5). Esse gradiente foi o mesmo para todos os subtipos, excluindo a hemorragia subaracnoídea. Para as mulheres, as taxas foram menores quando comparada aos homens e, o mesmo padrão foi observado para negras (125,4), pardas (88,5) e brancas (64,1). A razão de risco para homens negros quando comparado aos brancos foi 1.4, mas entre as mulheres negras e as brancas foi o dobro. Concluindo, houve um gradiente significativo da mortalidade cerebrovascular de acordo com raça, principalmente entre mulheres.